Identification of Sinorhizobium meliloti Genes Regulated during Symbiosis - Cabanes, Didier (American Society for Microbiology, 2000)
RNA fingerprinting by arbitrarily primed PCR was used to isolate Sinorhizobium meliloti genes regulated during the symbiotic interaction with alfalfa (Medicago sativa). Sixteen partial cDNAs were isolated whose corresponding genes were differentially expressed between symbiotic and free-living conditions. Thirteen sequences corresponded to genes up-regulated during symbiosis, whereas three were instead repressed during establishment of the symbiotic interaction. Seven cDNAs corresponded to known or predicted nif and fix genes. Four presented high sequence similarity with genes not yet identified in S. meliloti, including genes encoding a component of the pyruvate dehydrogenase complex, a cell surface protein component, a copper transporter, and an argininosuccinate lyase. Finally, five cDNAs did not exhibit any similarity with sequences present in databases. A detailed expression analysis of the nine non-nif-fix genes provided evidence for an unexpected variety of regulatory patterns, most of which have not been described so far.